(untitled) (Fiep Bulletin - online, 2015)
The purpose of this study was to analyze the force/resistance of superior members (FMS) and the fat percentage (%G) of scholars, from 7 to 11 years of age, from high socioeconomic level of Florianópolis, SC. The sample was constituted of 285 scholars of the fundamental teaching (130 male (45,6%) and 155 female (54,4%) of the public and private teaching system). In the constitution of the sample, the schools and the scholars were selected by convenience. The socioeconomic level was identified through the questionnaire of socioeconomic classification published by the National Association of Company of Research - ANEP (1997). In the collection of data the anthropometric measure was used (thickness of skinfolds), and the test of the modified bar, proposed by the FITNESSGRAM battery, of Cooper Institute for Aerobics Research (1999). The analysis of the data was accomplished through the descriptive statistics, variance analysis ANOVA One-Way, with the use of the test post hoc of Scheffé (p<0,05) and the test "t” of student for independent samples. The results evidenced that the girls obtained a larger fat percentage than the boys in all ages (p <0,05). In force/resistance of superior members (FMS) didn’t happen differences among the sexes, just among the ages 7 years-old with the 10 and 11 years-old for the boys and among the 7 years-old with the 10 years-old for the girls. Most of the scholars are inside of the criteria for health. However, it is important to point out that a considerable group, so much of the boys as of the girls, are below the criterion, supposing a tendency to the subjects related to the malnutrition.